An Analytical Mechanical Model of Corti in the Cochlea - Jiangtao Su; Wenjuan Yao; Zhengshan Zhao (Shock and Vibration)
The organ of Corti (OC) in the cochlea is a significant structure for feeling sound. The components of OC and the interaction of the part with the surroundings contribute to the fact that the passive tuning of the cochlear macrostructure is unclear. Based on the interaction between the basilar membrane (BM), tectorial membrane (TM), reticular lamina (RL), and various parts of OC, a mechanical model of the cochlea is established to study the motion patterns of each part under the action of a certain pressure. The variational principle is applied to the calculation of the analytical expression of the displacement of the BM. The results of the analytical solution differ little from the experimental value, and the variation trend is consistent, which presents the correctness of the model. The parameter sensitivity analysis is carried out for obtaining the interaction principle and the primary and secondary roles of each component in the process of the sense of sound. The results show that the absence of the TM and the decrease in the stiffness of the outer hair cells (OHCs) and OHC bundles will shift vibratory response patterns to lower frequencies, in which the lack of TM will result in the greatest reduction of CF. The absence of RL exerts a negative influence on the CF as well as the amplitude of BM and thereby loss of hearing. Therefore, both TM and RL are essential structures during the process of the sense of sound. At the same time, the resonance frequency at the base of the BM is concentrated on the high-frequency segment, while the apex of the BM is mainly in the low frequency. Different points of BM correspond to different CF, which demonstrates the frequency selectivity of the BM.